"You Look So Attractive!”: The Role of Interpersonal Attraction in Driving Customer Citizenship Behavior in Service Coproduction Process - Chan, Kimmy Wa; Sharma, Piyush (2019)
Practitioners’ and scholars’ interest in the service-dominant logic of marketing has increased sharply in the last decade (Vargo and Lusch 2004). Customer participation (CP), as one of the foundational premises of this service-dominant logic, enables service employees to cocreate customize services with customers to suit their needs (Auh et al. 2007; Chan, Yim, and Lam 2010; Yi, Nataraajan and Gong 2011). Extant research on the impact of CP is considerable, but with a dominant focus on taking from an extrinsically motivated perspective to examine the impact of CP on customer satisfaction or employees’ in-role performance through mechanisms of improved service quality, reduced costs, and enhanced control. However, the question of how CP might drive customers’ citizenship behaviors has not been well addressed. This question is important; firms experience remarkable challenges in their efforts to manage customer participation and cultivate more citizenship behaviors would help enhance their competitive advantage. This paper uses social exchange and reinforcement theories to explore the mediating role of interpersonal attraction, a crucial but under-researched relational construct that both parties can develop during the co-production process, in the impact of customer participation on customer citizenship behavior. Moreover, this research further examine the moderating roles of shared interpersonal similarity and coproduction task outcome on the relationship between customer participation and interpersonal attraction. With a large-scale survey data collected from customer-designer dyads from an interior design institution with multiple waves, results show that customer participation in the coproduction process with the employee will increase their citizenship behaviors through enhanced interpersonal attraction toward the employee. Particularly, such positive effect exists when the customer perceived a higher similarity with the employee, as supported by the positive reinforcement theory. Nevertheless, the moderation of perceived similarity is further altered by the coproduction task outcome such that the positive moderating effect of perceived similarity with the employee only functions well when the coproduction outcome is better than expected. This research extends the existing literatures in CP and value cocreation by studying customer citizenship behaviors as a more enduring and impactful outcomes for firm’s profitability and sustainability, which represents an important step in the effort to examine value co-creation processes more fully. It also enriches existing marketing literature by applying reinforcement theory to investigate the impact of CP on the creation of interpersonal attraction and customer citizenship behavior in a services context. Particularly, it explores the moderating roles of interpersonal similarity and co-production task outcomes on customer citizenship behaviors. Taken together, this research advances understanding of the complex relationship between CP and customer citizenship behaviors by showing that CP is a necessary, but not the only condition, for developing interpersonal attraction and customer citizenship behaviors and this process is moderated by other factors.